Centro de Atenção Psicossocial Infanto Juvenil - CAPSi - Silva, Fernanda Nathália Duque (FT - Faculdade de Tecnologia, 2022)
Mental health-related disorders are a concern with increasing attention in the population, being seen frequently in the media as well as a common discussion in the community. Mental disorders in childhood and adolescence are less discussed despite the growing recognition of psychiatric disorders. In the city of Manaus, the available child psychological care has a number below the necessary for care with little structure for the type of care needed and this absence of favorable architectural environments is also a cause of distance from the general population. In this way, to attract more users and expand the knowledge of this type of environment by the community and in the city, a new structuring of the project is proposed, with a more inviting and attractive way to passersby in the surroundings, thus using architecture to make the environment more pleasant and interesting for the people of the city.